Development of remote-controlled animations on 3D LED cube - Rahadian, Ghifari (2016)
Electromagnetism is an essential concept for for both scientists and engineers, especially electrical engineers. The design of antenna and electric magnet arises from this concept. However, it is found out that some students have a difficult time in grasping even the most fundamental concept of electromagnetism, such as electric force between two charges, direction of electric and magnetic field and the self-inducing nature of electromagnetic wave. Understanding those concepts require good visualization in 3-D, yet some students are simply weak in that visualization.